Atlas of Human Oocyte: A Review in the Daily In Vitro Fertilization (IVF) Practices - Silvia W Lestari (HM Publisher, 2023)
Background: Oocytes are gamete cells that play an important role in the daily practice of in vitro fertilization (IVF) laboratories. Oocyte morphology is important to study and assess in order to increase the success of IVF pregnancy. Methods: A computerized database search process in Pub med was performed to obtain data. Then, the most updated and relevant articles were selected. Results: Normal oocyte morphology should have normal-appearing cytoplasm, single polar body, appropriate zona pellucida (ZP) thickness, and appropriate perivitelline space (PVS). Abnormal oocyte morphology can be in the form of immature oocytes, large in size, ovoid or amorphous in shape, having fragment/double/multiple polar body I (PBI) and granular cytoplasm or smooth endoplasmic reticulum (SER). Conclusion: Abnormal oocyte morphology in the IVF laboratory can be seen by its maturity level, size, shape, condition of PBI, and cytoplasmic granularity. A better selection of oocytes can increase the performance of the IVF laboratory.